Series Fed Designs of Planar Circular and Hexagonal Microstrip Antenna Arrays for High Gain and Reduced First Side Lobe Level Radiation - Deshmukh,Sanjay B. (2022)
Abstract To achieve a high gain and low first side-lobe level, variants of linear and planar series fed circular and hexagonal microstrip antenna arrays using the binomial distribution, are proposed around 3000 MHz frequency band, on thinner Arlon substrate (h ~ 0.027λg). The linear 7 × 1 array of circular patches, yields first side-lobe level of −25 dB with a gain of 12.7 dBi, whereas using hexagonal patches, respective values are, −28 dB and 12.9 dBi. The planar 5 × 3 and 5 × 5 arrays using half wavelength and wavelength spacing are presented. An optimum response is obtained in 5 × 5 array for the wavelength inter-element spacing. Here, using circular patches, first side lobe level in the E and H-planes is −29 and −14 dB, respectively, with a peak gain of 17.6 dBi, whereas that using hexagonal patches, the respective first side lobe level in the E and H-planes is −26 and −17 dB, with a peak broadside gain of nearly 19 dBi. Thus using a thinner substrate, proposed series feed binomial planar arrays offer a gain of more than 15 dBi with a lower first side lobe level.